2012
DOI: 10.5513/jcea01/13.2.1059
|View full text |Cite
|
Sign up to set email alerts
|

Drought Tolerance of Bulgarian Common Bean Genotypes, Characterised by Some Biochemical Markers for Oxidative Stress

Abstract: The aim of this study was to characterize drought tolerance of 20 common bean genotypes using some biochemical markers for oxidative stress. 10 common bean cultivars (9 Bulgarian and a Mexican -BAT 477) and 10 mutant lines M (19)(20) , previously obtained by us after the treatment of seeds from Dobroudjanski 2 and Dobroudjanski 7 cultivars with ethyl methan sulphonate (EMS) and N-nithroso-N-ethyl urea (NEU) were used in this investigation. BAT 477 was chosen as a control and it was presented in unique cluster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Proline is one of the commonest osmolytes in plants, and seems to be a reliable marker of stress in Phaseolus, as in many other genera. Many reports have shown significant increases in Pro contents in Phaseolus plants submitted to water stress (23,24), but the correlation between Pro accumulation and stress tolerance remains unclear since apparently contradictory results have been reported using different bean varieties (25,26). The present study revealed that Pro accumulation is a common response to water stress in the four analysed bean cultivars, in agreement with the aforementioned published results.…”
Section: Discussionsupporting
confidence: 89%
“…Proline is one of the commonest osmolytes in plants, and seems to be a reliable marker of stress in Phaseolus, as in many other genera. Many reports have shown significant increases in Pro contents in Phaseolus plants submitted to water stress (23,24), but the correlation between Pro accumulation and stress tolerance remains unclear since apparently contradictory results have been reported using different bean varieties (25,26). The present study revealed that Pro accumulation is a common response to water stress in the four analysed bean cultivars, in agreement with the aforementioned published results.…”
Section: Discussionsupporting
confidence: 89%
“…The last biomarker of stress analysed was proline (Pro), a common osmolyte in plants, which accumulates in response to different types of abiotic stress, including drought, in a large number and variety of species [25,74]. Many studies reported significant increases in Pro contents in Phaseolus plants subjected to water stress [27][28][29][30]56], in which this osmolyte seems to be involved in the stress response but not in the tolerance mechanism. In the case of Lima bean, Arteaga et al [63] found higher Pro concentration in the cultivars more tolerant to salt stress, concluding that it could play an important role in their stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Proline (Pro) is one of the most common plant osmolytes [25,26]. A significant increase in Pro contents in response to water deficit, high salinity or other stressful conditions has been detected in many plant species, including beans [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, 18 genotypes, part of the available collection of the ethyl methane sulphonate (EMS) mutant lines from the Agricultural University-Plovdiv of Phaseolus vulgaris seed collection (Svetleva et al, 2012), and local Phaseolus spp. accessions from Bulgaria were selected based on morphological field observations and preliminary physiological and molecular data (Table 1).…”
Section: Plant Materialsmentioning
confidence: 99%